The Effect of Alcohol Intoxication on Mortality of Blunt Head Injury - Lin, Hsing-Lin (Hindawi Publishing Corporation, 2014)
Alcohol is found to have neuroprotection in recent studies in head injuries. We investigated the association of blood alcohol concentration (BAC) with mortality of patients with blunt head injury after traffic accident. All patients sustaining blunt head injury caused by traffic accident brought to our emergency department who had obtained a brain computed tomography scans and BAC were analyzed. Patients with unknown mechanisms, transfers from outside hospitals, and incomplete data were excluded. Logistic regression was used to identify independent predictors of mortality. During the study period, 3,628 patients with brain computed tomography (CT) were included. Of these, BAC was measured in 556 patients. Patients with the lowest BAC (less than 8 mg/dl) had lower mortality; intoxicated patients with BAC between 8 and less than 100 mg/dl were associated with significantly higher mortality than those patients in other intoxicated groups. Adjusted logistic regression demonstrated higher BAC group and Glasgow coma scale (GCS) scores, and lower ISS and age were identified as independent predictors of reduced mortality. In our study, we found that patients who had moderate alcohol intoxication had higher risk of mortality. However, higher GCS scores, lower ISS, and younger age were identified as independent predictors of reduced mortality in the study patients.